Vertical structure of heterotrophic bacterioplankton communities in the Western Pacific Ocean - Austria, Eleanor S.; Shiah, Fuh-Kwo; Awingan, Joan S.; Li, Kuo-Yuan; Wang, Ku-Wai; Chang, Chun-Wei (2019)
The abundance and composition of summer heterotrophic bacterioplankton communities at the Western Pacific Ocean (WPO) were determined using catalyzed-reporter deposition-fluorescence in situ hybridization (CARD-FISH) technique. Several oligonucleotide probes specific to the Domain Bacteria (EUB338), Phylum Proteobacteria (α-, β-, and γ-Proteobacteria and SAR 11); Actinobacteria (HGC); and Cytophaga-Flavobacter-Bacteroides (CFB) were used to identify and quantify the common bacterial phyla relative to total microbial abundance using 4? 6-diamidino-2-phenylindole (DAPI) over a depth profile?from 10 to 4000m. The profiles of microbial and bacterial abundance, temperature, and oxygen all decreased with depth, in contrast to the profiles of the inorganic compounds. Around 30?59% of the DAPI-positive cells took up the EUB338 probe, suggesting that bacteria are numerically significant components of the microbial biomass in the WPO. Phylum Proteobacteria was the predominant group in the whole water column, with classes α-and γ-Proteobacteria and SAR 11 numerically dominating at specific depths. Statistical analyses showed an association between the bacterial groups?α-Proteobacteria and CFB?and the environmental parameters?temperature and chlorophyll-a concentration?at the depth of 100m, suggesting the role of organic matter and temperature in structuring the bacterial community in this oceanic regime. This study provided a preview on the abundance and controls of specific groups of heterotrophic bacteria in the WPO, warranting a more detailed and comprehensive investigation of the community structure at clade or genus level. (Author's abstract)